A Question of Mercy : A Novel - Cox, Elizabeth, 1942- (Book collections on Project MUSE., 2016)
"Adam Finney, a young man who is mentally disabled, faces sterilization and lobotomy in a state-supported asylum. When he is found dead in the French Broad River of rural North Carolina, his teenaged stepsister, Jess, is sought for questioning by their family and the police. Jess's odyssey of escape across four states leads into dark territories of life-and-death moral choices where compassion and grace offer faint illumination but few answers. A Question of Mercy, set in a vivid landscape of the mid-twentieth-century South, is the fifth novel from Robert Penn Warren Award-winning writer Elizabeth Cox. As she challenges notions of individual freedom and responsibility against a backdrop of questionable practices governing treatment of the mentally disabled, she also stretches the breadth and limitations of the human heart to love and to forgive. Jess Booker, on the run and alone, leaves the comfort of her home near Asheville, recklessly trekking through woods and hitchhiking her way to a boarding house in tiny Lula, Alabama, a perceived safe haven she once visited with her late mother. Pursued by a mysterious car with a faded "I Like Ike" sticker, Jess is also haunted by memories of her mother's early death, her father's distressing marriage to Adam's mother, the loving bond she was able to form with Adam despite her initial resistance, and her boyfriend Sam's troubling letters from the thick of combat in the Korean War. In Lula, Jess finds, if only briefly, a respite among a curious surrogate family of fellow displaced outsiders banded together under one roof, and there she finds the strength to heed the call homeward to face the questions she cannot answer about her stepbrother's death. Through her vibrant depictions of characters in crisis and of the lush, natural landscapes of her southern settings, Cox brings to the fore the moral, ethical, and seemingly unnatural decisions people face when caring for society's weakest members. Grappling with the powerful bonds of love and family, A Question of Mercy recognizes the countless ways people come to help one another and the poor choices they can make because of love--choices that challenge the boundaries of human decency and social justice but also choices that can defy what is legal in the course of seeking what is right. Jill McCorkle, a Dos Passos Prize-winning novelist and short story writer and the author of Life after Life, provides a foreword to the novel."--